Brief Report: Rapid Clinical Recovery From Critical Coronavirus Disease 2019 With Respiratory Failure in a Pregnant Patient Treated With IV Vasoactive Intestinal Peptide. (5th January 2022) - Youssef, Jihad Georges; Bitar, Mohammad Z.; Zahiruddin, Faisal; Al-Saadi, Mukhtar; Elshawwaf, Mahmoud; Yau, Simon; Goodarzi, Ahmad; Javitt, Jonathan C.
Abstract : BACKGROUND: Aviptadil, a synthetic form of human vasoactive intestinal peptide, has entered clinical trials to treat critical coronavirus disease 2019 pneumonia with respiratory failure. Vasoactive intestinal peptide protects the lung against a broad array of injuries by binding to the vasoactive intestinal peptide receptor 1 receptor of alveolar type II cells, the cells that severe acute respiratory syndrome coronavirus 2 binds to. As the role of Aviptadil in treating pregnant patients with critical coronavirus disease 2019 pneumonia is unknown, the authors report successful treatment in such a patient who is ineligible for phase 3 trials of Aviptadil. CASE SUMMARY: Under an open-label Food and Drug Administration-approved Expanded Access Protocol NCT04453839, a 32-year-old female patient Gravida 6 Para 4 at 27-week gestation, body mass index 42.5 kg/m 2, admitted to the ICU of a quaternary care hospital with critical coronavirus disease 2019 was treated in January 2021 and followed for 4 months post-ICU admission. Standard of care included remdesivir, methylprednisolone, enoxaparin, and inhaled epoprostenol. In addition, the patient received three successive 12-hour IV infusions of Aviptadil at 50/100/150 pmol/kg/hr escalating doses, per randomized clinical trial NCT04311697. Human subjects' protection was overseen by the Institutional Review Board of the Houston Methodist Hospital. The patient was enrolled in the treatment and was given informed consent approved by the Food and Drug Administration and the Institutional Review Board. Data on the patient was incorporated based on her consent for de-identified data to be used in research given at the time of hospital admission in a manner approved by the Institutional Review Board (PRO00025607). Baseline inflammatory markers, arterial blood gases, radiologic imaging, oxygen requirements, Pao 2 /Fio 2, continuous fetal monitoring at baseline, throughout the patient's treatment with the investigational drug, and throughout the patient's hospital course. CONCLUSION: The rapid clinical improvement seen in this patient treated with IV vasoactive intestinal peptide is consistent with the theory that vasoactive intestinal peptide protects the alveolar type II cell, ameliorates cytokine storm, and improves oxygenation in acute lung injury. This specific role of vasoactive intestinal peptide in the lung may be vital to combating the lethal effects of severe acute respiratory syndrome coronavirus 2 infection. In addition, the role of vasoactive intestinal peptide in the human maternal-fetal interface suggests that vasoactive intestinal peptide is a safe treatment of severe coronavirus disease 2019 respiratory failure during pregnancy.